Work measurement analysis using Time Study Method to increase work productivity - Suci Aryani; Muthia Roza Linda (Operations Management and Information System Studies, 2023)
This study aims to analyze the work measurement in the process of working on pottery in Galogandang village using the stopwatch time study method. This measurement is carried out to determine the standard time of pottery processing and determine the optimal standard output. In this study, work measurements were carried out on competent 15 craftswomen. The data collection method is by observations and interviews. Based on calculations using a stopwatch time study, the results showed that the standard time for working on pottery was 126027.07 seconds or equal to 35.01 hours. Then the results for planning production targets using standard time are as many as 25 units/day for 8.88 work hours that can be a consideration or reference for pottery craftswomen to increase productivity.